Estado del arte; del uso de la eichhornia crassipes en la fitorremediación de aguas residuales industriales (2019)
Industrial wastewater requires control and management of its current production, according to existing literature, it is necessary that these are subjected to a quality treatment that works for continuous use and utilization, where it is also made an effective use of the water hyacinth floating macrofita (Eichhornia crassipes), which provides a treatment of industrial wastewater, obtaining high productivity and high efficiency of nutrient removal. This article aims to analyze the literature researched on macrophyte water hyacinth, involving, environmental sustainabili-ty, general aspects, background, design models, advantages and disadvantages, remediation, phytoremediation mechanism and current industrial wastewater treatment in the application of this phytoremediator method.